3-BOYUTLU KÜREDE HELİSEL GEODEZİKLİ YÜZEYLER - POYRAZ, MÜJGAN (Fırat Üniveristesi, 2010)
Bu çalışma iki bölümden oluşmaktadır.Birinci bölümde; bazı temel tanım ve teoremler verilmiştir.Ikinci bölümde; Riemann uzay formları ve helisel eğriler incelenmiştir. Ayrıca, heliselgeodezikler için bazı karakterizasyonlar elde edilip bunlarla ilgili yüzey örnekleriverilmiştir.

This thesis consist of two chapters.In the first chapter; are given some fundemental definitions and theorems.In the second chapter; are investigated Riemann space forms and helical curves. Inaddition, some characterizations are obtained for helical geodesics and surface examplerelated to helical geodesics are given
Surfaces which contain helical geodesics in the 3-sphere
Keywords: Matematik